PELATIHAN VARIASI TEKNIK BERMAIN SEPAKBOLA PADA SEKOLAH SEPAKBOLA (SSB) PUTRA TRESNA BALI - artawan, Kadek Suryadi (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2023)
Based on discussions with several SSB (Soccer School) Men's Tresna Bali coaches during football practice held at the Denpasar Flapa Field on October 28 2023, SSB students are expected to meet the requirements based on the PSSI. Coaches do not understand the variations and training stages of the Football Coaching Curriculum, and SSB students do not understand and master the training session model based on the PSSI Football Coaching Curriculum. Undirected soccer training programs and lack of knowledge are obstacles in developing quality young players in the future. Early childhood development is an important factor for countries to improve the quality of their senior players. Currently, the quality of early childhood education in Indonesia seems to be still low. Apart from that, some coaches and parents who have a big influence on children's interest in football still have minimal knowledge about how to use coaching information. The problems faced by the SSB Putra Tresna Denpasar City coach above are as follows: the coach is unable to organize and plan his training program properly based on the PSSI football coaching curriculum as well as a lack of coaching knowledge regarding training methods and stages. Football coaches, coaches do not yet understand and master the training session model based on the PSSI curriculum for football coaches. Based on these problems, training will focus on two aspects. SSB students will be able to understand the variations and stages of training based on the PSSI Football Coaching Curriculum. Second, so that SSB students understand and master the training session model based on the PSSI Football Coaching Curriculum. About the PSSI Curriculum for Football Coaches. The training program for implementing curriculum-based training programs is divided into five stages, namely the planning stage, activity implementation stage, observation stage, evaluation stage, and mentoring stage. This training activity will be carried out for four consecutive days, and of course mentoring activities will be carried out for two months after the activity. The target number of participants is 5 coaches and 32 SSB players, so the total is 37 people. The implementing partner for this service program is the Tresna Men's Football School (SSB) in Denpasar. Based on the results of the PKM football training activities, it shows that the suggestions in the problem formulation can be implemented well and appropriately. From the results of implementing this activity, there was an increase in knowledge and skills, as well as motivation and interest of young players and SSB Putra Tresna Bali students in practicing soccer games, especially basic variations. football playing techniques, the answer is high. This leads to improvement in personal skills of SSB students. Will be useful in the future